MODERNISASI TRANSPORTASI DAN MOBILITAS SOSIAL-EKONOMI DI JAWA BARAT: Dari Preanger Stelsel ke Jalur Kereta Api Tahun 1880–1930 - Syah, M. Kautsar Thariq; Sa’adah, Putri Lailatus; Nurcahya, Yan; Negara, Teddiansyah Nata; Murni , Fitria Eka Dewi (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2025)
This study analyzes the role of railway development in shaping regional integration and socio-economic transformation in West Java between 1880 and 1930. Employing a historical method with a qualitative, library-based approach, the research examines primary and secondary documents related to colonial transportation policies. The findings demonstrate that the transition from the Preanger Stelsel—a forced coffee cultivation system dependent on traditional transport networks—to modern railway infrastructure fundamentally altered patterns of mobility and economic exchange. The Dutch colonial administration introduced railway lines, maritime routes, and road systems to address logistical constraints caused by the long distance between inland plantations and coastal ports. The establishment of railways not only facilitated the efficient movementof plantation commodities and strengthened export capacity but also reconfigured spatial connectivity, enabling broader social mobility among local populations. The study argues that railway expansion served as a strategic instrument of colonial economic consolidation while simultaneously laying the groundwork for long-term regional integration in West Java.